Evaluation of the quality of superficial sediment using principal components analysis of the physical–chemical attributes of the Mearim River – Brazil - Lima, Neuriane Silva; Silva, Darlan Ferreira da; Nunes Neto, Wallace Ribeiro; Silva, Delmo Matos da; Sousa, Leila Cristina Almeida de; Silva, Maria Raimunda Chagas (Ciência e Natura, 2022)
The Mearim River is one of the main rivers of Maranhão, which, over the years, has been affected from pollution caused by human activities such as deforestation, disposal of domestic effluents, and agricultural activities, among others. The objective of this research was to evaluate the environmental quality of the Mearim River through the study of the sediment in different periods. In order to investigate this question, four sampling points (P1- Balneário, P2-Cais, P3-Trizidela, and P4-Matadouro) were submitted to particle size analysis (clay, silt, and fine sand) and physico-chemical analyses (pH, organic matter, and inorganic and organic carbon). Two principal components were generated in principal component analysis, explaining 73% of the total variance among the parameters within the studied periods. The overall analysis of the data set by principal component analysis highlighted two clusters: one relating the attributes to three sampling points analyzed in the rainy season and another relating the attributes to four sampling points analyzed in the dry period. Multivariate analysis of the data showed that the organic matter, clay, and pH parameters were directly correlated with the dry period (correlation coefficients> 0.41), and inorganic matter (correlation coefficient = | 0,414) was more sensitive in the rainy season.